Reflections on the relation between the city and the territory. the development of chicago and the great west (2006)
This article reviews the bond between city and territory from urban history perspective. The approach is focused mainly in the conditions and elements that contribute in the cities development, to say, naturegeography- material civilization, leaned on Chicago and the Great West development throughout the nineteenth century, case that results greatly exemplifying for the approach. Chicago is studied through a historical dimension concerned to the territory and the city conformation. Such approach is confronted to some determinism streams appeared to explain and outline developments taking place at that moment. The author uses the concepts of world-economy and geographic time, both analytic and historiography proposals exposed by Fernand Braudel, French historian of the Annals School, proposals introduced from a context history point of view and its phenomena, as the city seems to be. These concepts are face up to the current conceptions on the subject, introduced from an economic geography approach in urban studies. The prevailing necessity to include the historical point of view in these studies is aimed at understanding the city and the territory bonds.